Gremlin 1 — small protein, big impact: the multiorgan consequences of disrupted BMP antagonism†. Issue 4 (20th June 2020) - Gooding, Sarah; Leedham, Simon J
Abstract: Highly conserved, complex and interacting morphogen signalling pathways regulate adult stem cells and control cell fate determination across numerous different organs. In homeostasis, the bone morphogenetic protein (BMP) pathway predominantly promotes cell differentiation. Localised expression of ligand sequestering BMP antagonists, such as Gremlin 1 (Grem1), necessarily restricts BMP activity within the stem cell niche and facilitate stemness and self‐renewal. In a new paper, Rowan, Jahns et al show that acute deletion of Grem1 in adult mice, using a ubiquitous ROSA26‐Cre recombinase, induced not only severe intestinal enteropathy but also hypocellular bone marrow failure suggestive of stem cell niche collapse in both tissues. Grem1 has an increasingly recognised pleiotrophic role in a number of organ systems and is implicated across a wide range of disease states. Although the importance of Grem1 in intestinal stem cell regulation has been well described, a putative function in haematopoietic niche maintenance is novel and requires further exploration. Moreover, the complex and context‐specific regulation of Grem1, among a host of functionally convergent but structurally disparate BMP antagonists, warrants further research as we learn more about the pathogenic consequences of deranged expression of this small, but important, protein. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.